Analysis Of Factors Affecting The Intensity Of Octo-Mobile Usage By CIMB Niaga - Eka Ayu Agustina; Wita Juwita Ermawati; Rizal Ahmad Fauzi (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the factors that influence the intensity of use of Octo Mobile mobile banking by CIMB Niaga. This study identifies 8 variables, namely perceived useful-ness, perceived ease of use, interaction needs, perceived risk, perceived cost, trust, credi-bility and compatibility with lifestyle. Through hypothesis testing, this study confirmed the significant effect of these variables on the intensity of use of Octo Mobile. The results show that the most influential factor is compatibility with lifestyle and user needs. This indicates that users highly value the compatibility of mobile banking features with their daily banking activities and overall lifestyle. The next influential factor is the credibility of CIMB Niaga as a mobile banking service provider. Users perceive CIMB Niaga as a trustworthy institution, which ensures the security of personal information and transactions, thus increasing their confidence in using the service. The last influencing factor is perceived usefulness. Users feel that Octo Mobile by CIMB Niaga improves their job performance, makes banking tasks easier, and is overall useful. These findings suggest that to increase the intensity of Octo Mobile usage, CIMB Niaga needs to focus on improving the compatibility of the service with modern lifestyles, maintaining and enhancing credibility through strong security measures and transparent privacy policies, and continuing to innovate to add features that are useful and make users' banking activities easier. This strategic approach is expected to not only increase the intensity of usage but also directly proportional to the increase in bank revenue.